2018
DOI: 10.1038/s41598-018-22139-6
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A viruses alter the stability and antiviral contribution of host E3-ubiquitin ligase Mdm2 during the time-course of infection

Abstract: The interplay between influenza A viruses (IAV) and the p53 pathway has been reported in several studies, highlighting the antiviral contribution of p53. Here, we investigated the impact of IAV on the E3-ubiquitin ligase Mdm2, a major regulator of p53, and observed that IAV targets Mdm2, notably via its non-structural protein (NS1), therefore altering Mdm2 stability, p53/Mdm2 interaction and regulatory loop during the time-course of infection. This study also highlights a new antiviral facet of Mdm2 possibly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Furthermore, and similar to what some of the CoV PLpro's may do (see above in this section), Influenza NS1 was recently shown to destabilize Mdm2 E3 ligase which somehow benefits the IAV infection. According to the authors, this is because Mdm2 seems to have a p53-independent antiviral function which is then alleviated [130]. This is, however, in contrast to what was mentioned for NL63 CoV, where PLpro seems to stabilize Innate Immune Evasion by Respiratory Viruses Mdm2 to also benefit infection [124].…”
Section: Manipulation Of Ubiquitin and Isg15 Regulated Innate Immune mentioning
confidence: 91%
“…Furthermore, and similar to what some of the CoV PLpro's may do (see above in this section), Influenza NS1 was recently shown to destabilize Mdm2 E3 ligase which somehow benefits the IAV infection. According to the authors, this is because Mdm2 seems to have a p53-independent antiviral function which is then alleviated [130]. This is, however, in contrast to what was mentioned for NL63 CoV, where PLpro seems to stabilize Innate Immune Evasion by Respiratory Viruses Mdm2 to also benefit infection [124].…”
Section: Manipulation Of Ubiquitin and Isg15 Regulated Innate Immune mentioning
confidence: 91%
“…At the same time, there is a constant threat of newly emerging highly virulent pandemic strains. 1,2 "Vaccines have saved hundreds of millions of lives over the last century, and influenza has an important place in preventive health care programs. One estimate looking at excess deaths attributed to influenza found that, in milder influenza seasons, there were around 8 deaths per 100,000 population, while in more severe but non-pandemic years, the figure would be 44 per 100,000 3.…”
Section: Introductionmentioning
confidence: 99%
“…It might be worthwhile to investigate whether the virus generates the stratagem to counteract this inhibitory effect during evolution. It has been reported that the protein level of HDM2 was not affected after infection of H3N2 in MDCK cells [31]. Interestingly, in H3N2-infected A549 cells, HDM2 expression level decreased at early stages of infection, while it is dramatically increased at 24 h post-infection [32].…”
Section: Discussionmentioning
confidence: 99%